Multi-aspect testing and ranking inference to quantify dimorphism in the cytoarchitecture of cerebellum of male, female and intersex individuals: a model applied to bovine brains - L. Corain; E. Grisan; J.-M. Graïc; R. Carvajal-Schiaffino; B. Cozzi; A. Peruffo (Brain Structure and Function, 2020)
The dimorphism among male, female and freemartin intersex bovines, focusing on the vermal lobules VIII and IX, was analyzed using a novel data analytics approach to quantify morphometric differences in the cytoarchitecture of digitalized sections of the cerebellum. This methodology consists of multivariate and multi-aspect testing for cytoarchitecture-ranking, based on neuronal cell complexity among populations defined by factors, such as sex, age or pathology. In this context, we computed a set of shape descriptors of the neural cell morphology, categorized them into three domains named size, regularity and density, respectively. The output and results of our methodology are multivariate in nature, allowing an in-depth analysis of the cytoarchitectonic organization and morphology of cells. Interestingly, the Purkinje neurons and the underlying granule cells revealed the same morphological pattern: female possessed larger, denser and more irregular neurons than males. In the Freemartin, Purkinje neurons showed an intermediate setting between males and females, while the granule cells were the largest, most regular and dense. This methodology could be a powerful instrument to carry out morphometric analysis providing robust bases for objective tissue screening, especially in the field of neurodegenerative pathologies.

Emerging roles of radioresistance in prostate cancer metastasis and radiation therapy - Lei Chang; Peter H. Graham; Jingli Hao; Joseph Bucci; Paul J. Cozzi; John H. Kearsley; Yong Li (Cancer and Metastasis Reviews, 2014)

Density and habitat use of lions and spotted hyenas in northern Botswana and the influence of survey and ecological variables on call-in survey estimation - G. Cozzi; F. Broekhuis; J. W. McNutt; B. Schmid (Biodiversity and Conservation, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Paraoxonase 1 L55M, Q192R and paraoxonase 2 S311C alleles in atherothrombosis - L. Cozzi; J. Campolo; M. Parolini; R. De Maria; M. C. Patrosso; A. Marocchi; O. Parodi; S. Penco (Molecular and Cellular Biochemistry, 2013)

Role of the EpCAM (CD326) in prostate cancer metastasis and progression - Jie Ni; Paul J. Cozzi; Wei Duan; Sarah Shigdar; Peter H. Graham; Kearsley H. John; Yong Li (Cancer and Metastasis Reviews, 2012)

MUC1, MUC2, MUC4, MUC5AC and MUC6 Expression in the Progression of Prostate Cancer - Paul J. Cozzi; Jian Wang; Warick Delprado; Alan C. Perkins; Barry J. Allen; Pamela J. Russell; Yong Li (Clinical & Experimental Metastasis, 2005)

Temperature-activity relationship for the intestinal Na+-K+-ATPase of Sparus aurata. A role for the phospholipid microenvironment? - E. Almansa; J. J. Sánchez; S. Cozzi; C. Rodríguez; M. Díaz (Journal of Comparative Physiology B, 2003)

Segmental heterogeneity in the biochemical properties of the Na + -K + -ATPase along the intestine of the gilthead seabream ( Sparus aurata L.) - Almansa E.; Sanchez J.; Cozzi S.; Casariego M.; Cejas J.; Díaz M. (Journal of Comparative Physiology B, 2001)

A trisomic germ cell line and precocious chromatid segregation leads to recurrent trisomy 21 conception - J. Cozzi; Clare M. Conn; Joyce Harper; Robert M. L. Winston; M. Rindl; Peter A. Farndon; J. D. A. Delhanty (Human Genetics, 1999)

Meiotic behaviour of sex chromosomes investigated by three-colour FISH on 35 142 sperm nuclei from two 47,XYY males - E. Chevret; S. Rousseaux; M. Monteil; Y. Usson; J. Cozzi; R. Pelletier; B. Sèle (Human Genetics, 1997)